Design of an Alphabet to Braille Letter Conversion Board Android based - Ferry Yoga Pratama; Miftachul Ulum; Haryanto; Deni Tri Laksono (JOINCS (Journal of Informatics, Network, and Computer Science), 2021)
A blind person is someone who has problems in terms of vision. This can occur due to congenital factors or disease factors that can affect the eye. To be able to replace the role of the eye to read something, blind people are known as a writing system known as Braille. Braille letters are letters specially designed for blind people. The introduction of Braille letters has been carried out since the beginning by special school teachers using Braille cards. Due to the large number of characters, the card arrangement often seems to take time to find the desired character. The arrangement of cards like this means that learning can only be done in a special school environment and cannot be done by someone who is not a special school teacher. To assist teachers in teaching and to help ordinary people teach Braille to the blind, a tool called the Android-based conversion board for the alphabet to Braille is made.